PENGARUH DESA DESENTRALISASI KEUANGAN TERHADAP KINERJA KEUANGAN DAN IMPLIKASINYA PADA AKUNTABILITAS MANAJEMEN KEUANGAN DESA - Prima Reza Wahyuni; Eni Duwita Sigalingging (Mount Hope Management International Journal, 2024)
The aim of this research is to analyze the village's original income, savings and other resources, as well as the village's financial performance and village responsibilities in managing village finances. Sampling was purposive sampling of a population of 127 villages in Padang Pariaman district. The research sample consisted of 20 villages included in the "Developing Villages" category. The variables used in this research are initial village income, transfer funds, other funds, financial performance, and accountability. The findings explain that the village's initial income influences financial performance and responsibility. The movement of these funds affects financial performance. There are no other variables in the fund that affect financial performance or accountability. Financial performance variables have no effect on accountability